Glyoxal observations in the global marine boundary layer. Issue 10 (16th May 2014) - Mahajan, Anoop S.; Prados‐Roman, Cristina; Hay, Timothy D.; Lampel, Johannes; Pöhler, Denis; Groβmann, Katja; Tschritter, Jens; Frieß, Udo; Platt, Ulrich; Johnston, Paul; Kreher, Karin; Wittrock, Folkard; et al.
Abstract Glyoxal is an important intermediate species formed by the oxidation of common biogenic and anthropogenic volatile organic compounds such as isoprene, toluene, and acetylene. Although glyoxal has been shown to play an important role in urban and forested environments, its role in the open ocean environment is still not well understood, with only a few observations showing evidence for its presence in the open ocean marine boundary layer (MBL). In this study, we report observations of glyoxal from 10 field campaigns in different parts of the world's oceans. These observations together represent the largest database of glyoxal in the MBL. The measurements are made with similar instruments that have been used in the past, although the open ocean values reported here, average of about 25 parts per trillion by volume (pptv) with an upper limit of 40 pptv, are much lower than previously reported observations that were consistently higher than 40 pptv and had an upper limit of 140 pptv, highlighting the uncertainties in the differential optical absorption spectroscopy method for the retrieval of glyoxal. Despite retrieval uncertainties, the results reported in this work support previous suggestions that the currently known sources of glyoxal are insufficient to explain the average MBL concentrations. This suggests that there is an additional missing source, more than a magnitude larger than currently known sources, which is necessary to account for the observed atmospheric levels of glyoxal. Therefore, it could play a more important role in the MBL than previously considered.